New and emerging lipid-modifying drugs to lower LDL cholesterol - Constantine E Kosmas; Dafni Pantou; Andreas Sourlas; Evangelia J Papakonstantinou; Rogers Echavarria Uceta; Eliscer Guzman (BioExcel Publishing Ltd, 2021)
Cardiovascular disease (CVD) represents the leading cause of death worldwide. The role of low-density lipoprotein-cholesterol (LDL-C) in the pathophysiology of atherosclerosis and CVD has been well recognized. Statins are the standard of care for the management of hypercholesterolaemia, and their effectiveness in lowering LDL-C and reducing CVD risk in both primary and secondary prevention has been well established. However, several patients fail to attain optimal LDL-C goals or are intolerant to statins, especially at high doses. PCSK9 inhibitors, bempedoic acid, inclisiran, ANGPTL3 inhibitors, PPARβ/δ agonists and LXR agonists are novel or upcoming LDL-C-lowering agents that have shown promising beneficial results. This review aims to present and discuss the current clinical and scientific data pertaining to the new and emerging lipid-modifying LDL-C-lowering drugs.